2010
DOI: 10.1021/jp106384e
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-Dependent Phase Transition and Piezoelectric Response in Textured Nb-Doped Pb(Zr0.52Ti0.48)O3 Thin Films

Abstract: [100]-textured Nb-doped Pb(Zr0.52Ti0.48)O3 (PNZT) films with different thicknesses from 80 to 600 nm were fabricated on Pt(111)/Ti/SiO2/Si(100) substrates by a sol−gel process. It was found that the local effective longitudinal piezoelectric coefficient, d 33, initially increased with film thickness and reached a peak (∼220 pm/V) for an intermediate thickness (∼350 nm), but then decreased with further increasing thickness. XRD and Raman analyses revealed that, even for an identical Zr/Ti ratio of 52/48, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…15,31,32 This is not surprising as the large ferroelectric response can be attributed to these following comprehensive reasons: First, the present thin films show an excellent epitaxial growth mode on STO(111) substrates, which can manifest superior electrical properties than those polycrystalline thin films growing on silicon substrates, meanwhile the [111]-oriented films show higher ferroelectric response than [100]-oriented cases as mentioned before. Then, it has been confirmed that the MPB moved to Ti-rich region near the Zr/Ti ratio of 30/70, the extrinsic contribution originating from domain motions is believed to be a significant component of the large ferroelectric response at the MPB region.…”
Section: B Ferroelectric Propertysupporting
confidence: 62%
See 1 more Smart Citation
“…15,31,32 This is not surprising as the large ferroelectric response can be attributed to these following comprehensive reasons: First, the present thin films show an excellent epitaxial growth mode on STO(111) substrates, which can manifest superior electrical properties than those polycrystalline thin films growing on silicon substrates, meanwhile the [111]-oriented films show higher ferroelectric response than [100]-oriented cases as mentioned before. Then, it has been confirmed that the MPB moved to Ti-rich region near the Zr/Ti ratio of 30/70, the extrinsic contribution originating from domain motions is believed to be a significant component of the large ferroelectric response at the MPB region.…”
Section: B Ferroelectric Propertysupporting
confidence: 62%
“…Previous studies declared that the mismatch strain would change the location of MPB region. 14,15 Our preceding study reported an interesting finding in [001]-oriented epitaxial PNZT thin films on [100]-cut STO singlecrystalline substrates, in which the MPB composition shifted to a higher Zr content region (Zr/Ti $ 70/30), whereby the highest electrical properties were obtained. 16 According to theoretical analysis, the tetragonal phase was more preferable to deposit on [100]-cut STO substrate for a smaller lattice mismatch than the rhombohedral phase, while the rhombohedral phase was predominant on 5 ] as raw materials together with 2-methoxyethanol, acetylacetone, and methanamide as solvent, chelating agent, and stabilizing agent, respectively.…”
Section: Thin Films I Introductionmentioning
confidence: 99%
“…7. The data revealed an evolution in the grain size with the variation of PZTNi30 film thickness, and the main features from AFM images can be summarized as follows: (i) PZTNi30 5-nm films on ITO/glass substrate have small grains compared with the other films; (ii) for 25-nm and 50-nm PZTNi30 films, the small grains start to agglomerate to form large grains; (iii) 100-nm films show clearly a large grain structure embedded with small grains with round shapes (see white arrows in enlarged grain in inset); (iv) 400-nm films present well-defined grain structure with distinct grain boundaries; (v) from Table I thin films by Li et al 50 and Majumder et al, 43 respectively. The change in grain size with thickness may be due to (i) small grains coalesce into the larger grains as the thickness of the PZTNi30 increases, and (ii) high stress developed in the film due to the lattice mismatch between film and substrate.…”
Section: Optical Characterizationmentioning
confidence: 96%
“…Among lead‐free piezoelectric ceramics, potassium sodium niobate, (K, Na)NbO 3 (KNN), is one of the most promising candidates with competitive piezoelectric properties over a broad temperature range, as obtained in KNN‐based bulk ceramics by constructing phase coexistence with complex chemical compositions . Compared to the bulk counterparts, it is much more challenging to achieve excellent piezoelectric properties in KNN‐based thin films, because of the difficulties in controlling composition and phase coexistence with much more severe volatility issues, and more complicated stress and thickness effects …”
Section: Introductionmentioning
confidence: 99%